Maternal mortality and COVID-19 - Takemoto, Maira L. S. [UNESP]; Menezes, Mariane O. [UNESP]; Andreucci, Carla B.; Knobel, Roxana; Sousa, Liduína A. R.; Katz, Leila; Fonseca, Eduardo B.; Magalhães, Claudia G. [UNESP]; Oliveira, Wanderson K.; Rezende-Filho, Jorge; Melo, Adriana S. O.; Amorim, Melania M. R. (Taylor & Francis, 2020)
Objective: The aim of this study was to collect and analyze data from different sources to have a general overview of COVID-19-related maternal deaths in Brazil, as well as to compare data with worldwide reports. Study design: We systematically searched data about COVID-19 maternal deaths from the Brazilian Ministry of Health surveillance system, State Departments of Health epidemiological reports, and media coverage. Data about timing of symptom onset and death (pregnancy or postpartum), gestational age, mode of birth, maternal age, comorbidities and/or risk factors, date of death, and place of death were retrieved when available. Results: We identified 20 COVID-19-related maternal deaths, age range 20–43 years. Symptoms onset was reported as on pregnancy for 12 cases, postpartum for 3 cases, and during the cesarean section for 1 case (missing data for 4). In 16 cases, death occurred in the postpartum period. At least one comorbidity or risk factor was present in 11 cases (missing data for 4). Asthma was the most common risk factor (5/11). Ten cases occurred in the Northeast region, and nine cases occurred in the Southeast region (5 of them in São Paulo, the first epicenter of COVID-19 in the country). Conclusions: To the best of our knowledge, this is the largest available series of maternal deaths due to COVID-19. Barriers to access healthcare, differences in pandemic containment measures in the country and high prevalence of concomitant risk factors for COVID-19 severe disease may play a role in the observed disparity compared to worldwide reports on maternal outcomes.
Keywords: coronavirus; COVID-19; maternal mortality; postpartum period; pregnancy; severe acute respiratory syndrome coronavirus 2